Pengaruh Senam Disminore Terhadap Skala Nyeri Disminore pada Remaja Putri Di Dusun Kenayan Wedomartani, Ngemplak, Sleman DIY - Liliana, Anita; Fitriana, Lala Budi; Syahidah, Nurul Febrina (Universitas Harapan Bangsa Purwokerto, 2022)
Background : One of the problems often faced by young women is menstrual pain (dysmenorrhea). The rate of dysmenorrhea in the world is very large, on average more than 50% of women in every country experience dysmenorrhea. In Indonesia, the incidence of dysmenorrhea is found as much 64.25%, most commonly found in adolescents. Altough generally harmless, it can interfere with daily activities. In addition to using pharmacology, dysmenorrhea can be overcome with non-pharmacological techniques, namely by doing dysmenorrhea exercises. Objective : To determine the effect of dysmenorrhea exercise on pain scale during dysmenorrhea in adolescent girls in Kenayan Hamlet, Wedomartani, Ngemplak, Sleman DIY. Methods : The research design used a quasi-experimental design with pre-test and post-test design without control. The subjects of the study were the young women of the village of Kenayan who experienced dysmenorrhea as many as 38 respondents. Pain scale is measured by NRS. Statistical test using T-Tes Pired Test. Results : The pain scale before the dysmenorrhea exercise is done 5,00 ±1727 (1-9) and after the dysmenorrhea exercise is done it is 2,00±1,109 (0-4). Based on the Paired T-Test, it is known that the p-value = 0,000. Conclusion : There is an effect of dysmenorrhea exercise on the scale of dysmenorrhea in young women in the village of Kenayan. Keywords : Dysmenorrhea Gymnastics,Pain, Youth